THE IMPORTANCE AND ROLE OF EFFECTIVE COMMUNICATION SKILLS IN LANGUAGE TEACHING - Barchinoy Abduraxmatovna Xamrakulova; Maria Pilar Escudero (Modern American Journals, 2025)
This article explores the significance of communicative competence in the teaching of foreign languages, emphasizing its central role in fostering effective communication skills among learners. It examines the most widely used teaching methods in language education and discusses their relevance and effectiveness in classroom settings. The paper also highlights the importance of selecting appropriate teaching techniques and applying them correctly to enhance the learning experience. Various viewpoints are presented regarding methodological approaches, aiming to contribute to the improvement of pedagogical practices in foreign language instruction.
Keywords: language, teaching, education, methods, pedagogy, communicative competence, language acquisition